Level of Student Satisfaction with Facilities Education with Tuition as a Moderation Variable - Nur Qoudri Wijaya; Moh. Baqir Ainun; Dedy Arfiyanto (International Journal Labs, 2023)
The sustainability of a company, both manufacturing, trading, and service companies, will not be separated from the role and existence of consumers they have. The purpose of this study is to determine the effect of educational facilities on student satisfaction with education costs as a moderation variable. This study used a questionnaire that was distributed to all students at Wiraraja Madura University. Data analysis was performed using SmartPLS Structural Equation Modelling (SEM) at a significant rate of 5%. The results showed that educational facilities and education costs had a significant effect on student satisfaction at Wiraraja University. However, tuition fees were not shown to be a moderating variable on the relationship between educational facilities and student satisfaction. Based on the results of descriptive statistical analysis, it can also be seen that the level of student satisfaction at Wiraraja University is between the categories of quite satisfactory to satisfactory. This shows that in general, Wiraraja University has been able to provide good educational facilities. However, it is known that the indicator of educational facilities that has the lowest statistical t value is the hotspot area. Therefore, Wiraraja University should pay more attention to the quality of hotspot areas to increase student satisfaction. This research focuses on Wiraraja Madura University, this is intended so that the research results can be used for management decision-making at Wiraraja University.